The prevalence of obesity and overweight, associated demographic and lifestyle factors, and health status in the adult population of Jeddah, Saudi Arabia. (September 2019) - Al-Raddadi, Rajaa; Bahijri, Suhad M.; Jambi, Hanan A.; Ferns, Gordon; Tuomilehto, Jaakko
Background: Obesity is a risk factor for many chronic diseases, and its prevalence and trends vary among populations. Saudi Arabia shows a greater rise in prevalence than many other countries. We aimed to study the association between several chronic disorders, demographic, and lifestyle factors with increased body mass index (BMI) in the adult population of Jeddah. Methods: Data were obtained from a door-to-door cross sectional study. A three-stage stratified cluster sampling technique was adopted. Individuals in selected households agreeing to participate were interviewed to complete a predesigned questionnaire covering demographic and lifestyle variables, medical history, and family history of chronic diseases. This was followed by anthropometric and blood pressure measurements. A random capillary plasma glucose (RPG) was measured, followed by further testing using fasting plasma glucose and glycated hemoglobin (HbA1c) to verify whether participants were normal, diabetic, or prediabetic. Multiple logistic regression analyses were used to adjust for confounding factors. Results: A total of 1419 individuals were included in the study: 667 men and 752 women. The prevalence of overweight and obesity was 35.1 and 34.8%, respectively, in men, and 30.1% and 35.6%, respectively, in women. Both overweight and obesity increased in prevalence to 60 years of age, and decreased in the oldest age group in both sexes. After adjusting for age, risk of obesity in men was increased with having a postgraduate degree [odds ratio (OR), 95%CI = 2.48, 1.1–5.61] and decreased with increased physical activity (OR, 95%CI = 0.49, 0.26–0.91). Risk of prediabetes and diabetes was increased in obese women (OR, 95%CI = 2.94, 1.34–6.44, and 3.61, 1.58–8.26 respectively), that of hypertension in obese men (OR, 95%CI =2.62, 1.41–4.87), and that of dyslipidemia in both sexes (OR, 95%CI = 2.60, 1.40–4.83 in men, and 2.0, 1.01–3.85 in women). A family history of dyslipidemia was associated with reduced risk of obesity among women (OR, 95%CI = 0.33, 0.12–0.92), whereas, in people with above normal weight (BMI ⩾25), there was increased risks of prediabetes, diabetes, and dyslipidemia among women (OR, 95%CI = 2.50, 1.21–5.17; 3.20, 1.45–7.03, and 1.88, 1.02–3.49, respectively ), and of hypertension among men (OR, 95%CI = 1.80, 1.00–3.23). Conclusions: The prevalence of overweight and obesity in the Saudi population remain high, indicating ineffectiveness or lack of preventive measures. Risk of prediabetes, diabetes, dyslipidemia, and hypertension increased with increasing BMI, with some sex differences in these associations.